2013
DOI: 10.5951/jresematheduc.44.4.0683
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Content Organization and Curriculum Implementation on Students' Mathematics Learning in Second-Year High School Courses

Abstract: We examined curricular effectiveness in high schools that offered parallel paths in which students were free to study mathematics using 1 of 2 content organizational structures, an integrated approach or a (traditional) subject-specific approach. The study involved 3,258 high school students, enrolled in either Course 2 or Geometry, in 11 schools in 5 geographically dispersed states. We constructed 3-level hierarchical linear models of scores on 3 end-of-year outcome measures: a test of common objectives, an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…Some research has found that curriculum-specific professional development is a significant factor in predicting effectiveness (Schoen, Cebulla, Finn, & Fi, 2003), though other research has not found such effects (Tarr, Grouws, Chavez, & Soria, 2013). In the context of state level reform in California, Cohen and Hill (2001) found that the things that made a difference to changes in their practice were integral to instruction: curricular materials for teachers and students to use in class; assessments that enabled students to demonstrate their mathematical performance-and teachers to consider it-and instruction for teachers that was grounded in these curriculum materials and assessments.…”
Section: Teachers' Use Of Curriculummentioning
confidence: 99%
“…Some research has found that curriculum-specific professional development is a significant factor in predicting effectiveness (Schoen, Cebulla, Finn, & Fi, 2003), though other research has not found such effects (Tarr, Grouws, Chavez, & Soria, 2013). In the context of state level reform in California, Cohen and Hill (2001) found that the things that made a difference to changes in their practice were integral to instruction: curricular materials for teachers and students to use in class; assessments that enabled students to demonstrate their mathematical performance-and teachers to consider it-and instruction for teachers that was grounded in these curriculum materials and assessments.…”
Section: Teachers' Use Of Curriculummentioning
confidence: 99%
“…Selain tujuan, penentuan dan pengorganisasian konten juga melibatkan kriteria lain, seperti validitas (keabsahan), makna (signifikansi), perbedaan yang tepat antara berbagai tingkatan dan konten, dan tingkat perkembangan. Lebih jauh lagi, kontinuitas dan urutan dalam belajar dan variasi kapasitas belajar penting pula untuk dipertimbangkan (Bahri, 2014;Kuboja & Ngussa, 2015;Taba, 1962).…”
Section: Landasan Kurikulumunclassified
“…(2002) showed that textbook is a potentially implemented curriculum that forges a direct link between intended and implemented curricula. Many studies also asserted that mathematics textbooks play a key role in mathematics teaching and learning process (Fan et al., 2013; Tarr et al., 2013; Wijaya et al, 2015), as mathematics textbooks are a major source of information and learning for teachers and students.…”
Section: Introductionmentioning
confidence: 99%
“…We can reveal possible opportunities to learn mathematics intended for students in different countries through textbooks analysis and comparison because textbooks are regarded as the embodiment of such intention in mathematics curriculum or mathematics standards (Choi & Park, 2013). Törnroos (2005) suggested that learning opportunities should be considered as an important factor to explain the differences of students’ performance in mathematics among different countries; this implies that if the contents of textbooks are designed differently, students will receive different opportunities to learn mathematics (Haggarty & Pepin, 2002; Tarr et al., 2013). The differences in opportunity to learn partly generate the emergence of different mathematics performance; earlier studies have confirmed this assumption, in which mathematics textbooks have a strong relationship with students’ mathematics performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation